Metformin and Bone Metabolism in Endogenous Glucocorticoid Excess: An Exploratory Study - Vogel, Frederick; Braun, Leah; Rubinstein, German; Zopp, Stephanie; Oßwald, Andrea; Schilbach, Katharina; Schmidmaier, Ralf; Bidlingmaier, Martin; Reincke, Martin (Frontiers in Endocrinology, 2021)
Context: Glucocorticoid excess exhibits multiple detrimental effects by its catabolic properties. Metformin was recently suggested to protect from adverse metabolic side-effects of glucocorticoid treatment. Whether metformin is beneficial in patients with endogenous glucocorticoid excess has not been clarified. Objective: To evaluate the phenotype in patients with endogenous Cushing’s syndrome (CS) treated with metformin at the time of diagnosis. Patients and methods: As part of the German Cushing’s Registry we selected from our prospective cohort of 96 patients all 10 patients who had been on pre-existing metformin treatment at time of diagnosis (CS-MET). These 10 patients were matched for age, sex and BMI with 16 patients without metformin treatment (CS-NOMET). All patients had florid CS at time of diagnosis. We analyzed body composition, metabolic parameters, bone mineral density and bone remodeling markers, muscle function and quality of life. Results: As expected, diabetes was more prevalent in the CS-MET group, and HbA1c was higher. In terms of comorbidities and the degree of hypercortisolism, the two groups were comparable. We did not observe differences in terms of muscle function or body composition. In contrast, bone mineral density in metformin-treated patients was superior to the CS-NOMET group at time of diagnosis (median T-Score -0.8 versus -1.4, p = 0.030). CS-MET patients showed decreased β-CTX levels at baseline (p = 0.041), suggesting reduced bone resorption under metformin treatment during glucocorticoid excess. Conclusion: This retrospective cohort study supports potential protective effects of metformin in patients with endogenous glucocorticoid excess, in particular on bone metabolism.